(untitled) (Medical Forum Monthly, 2024)
Objective: To assess infection control practices in Karachi, Pakistan. To investigate personal protective equipment such as gloves, mask and protective eye wear used in dental practice in Karachi, Pakistan Study Design: Cross sectional descriptive study. Place and Duration of Study: This study was carried out in Dental colleges, hospitals and private clinics of Karachi, Pakistan from January to March 2013. Materials and Methods: A pre coded questionnaire was used to collect data from dentists working in different work places. The study included dentists working in Dental colleges, Hospitals and private clinics. Undergraduate dental students and dentists not having PMDC registration were excluded from the study. Total 251 completed questionnaires were obtained. The dentists filled the questionnaire and were categorized into three groups Specialist group, Post graduate trainees group and General dentists group, according to their qualifications. Descriptive statistics were computed and differences between groups were assessed through Chi square test using SPSS version 16.0. Results: Statistically significant differences were observed in infection control practices of various groups of dentists regarding use of personal protective equipment, surface disinfection between Patients, disinfecting outgoing lab cases, use of sterilization wrappings and use of Sharps disposal system. Conclusion: Infection control practices of the three groups of dentists were different. More over the infection control practices of dentists working in different work places was also different